NADPH Oxidase Deficiency: A Multisystem Approach. (21st December 2017) - Giardino, Giuliana; Cicalese, Maria Pia; Delmonte, Ottavia; Migliavacca, Maddalena; Palterer, Boaz; Loffredo, Lorenzo; Cirillo, Emilia; Gallo, Vera; Violi, Francesco; Pignata, Claudio
Abstract : The immune system is a complex system able to recognize a wide variety of host agents, through different biological processes. For example, controlled changes in the redox state are able to start different pathways in immune cells and are involved in the killing of microbes. The generation and release of ROS in the form of an "oxidative burst" represent the pivotal mechanism by which phagocytic cells are able to destroy pathogens. On the other hand, impaired oxidative balance is also implicated in the pathogenesis of inflammatory complications, which may affect the function of many body systems. NADPH oxidase (NOX) plays a pivotal role in the production of ROS, and the defect of its different subunits leads to the development of chronic granulomatous disease (CGD). The defect of the different NOX subunits in CGD affects different organs. In this context, this review will be focused on the description of the effect of NOX2 deficiency in different body systems. Moreover, we will also focus our attention on the novel insight in the pathogenesis of immunodeficiency and inflammation-related manifestations and on the protective role of NOX2 deficiency against the development of atherosclerosis.